The potential of the Sorb (Sorbus domestica L.) as a minor fruit species in the Mediterranean areas: description and quality traits of underutilized accessions - Sottile, Francesco; Del Signore, Maria Beatrice; Giuggioli, Nicole Roberta; Peano, Cristiana (Progress in Nutrition, 2017)
Biodiversity linked to fruit cultivation plays a key role in terms of the availability of quality products and nutraceutical compounds for the food industry. Thus underutilized species such as Sorbus domestica L. can be an important resource. The aim of this study was to evaluate 31 local accessions from different growing areas on the Island of Sicily and characterize the fruits according to the biometric-carpological features that constitute their quality in order to understand the potential that this species may have not only regarding the recovery and preservation of genetic resources in the Mediterranean area but also the nutraceutical compounds it offers. The results from this preliminary study showed significant differences in quality between the considered accessions and suggested that these local varieties are a good source of total polyphenol compounds.